Behavioural risk factors of non-communicable diseases among adolescents - Adhikari, K; Adak, MR (Journal of Institute of Medicine Nepal, 2013)
Introduction: Cardiovascular and other chronic diseases are becoming the major causes of morbidity and mortality in most of the third world countries, including Nepal. Unhealthy diet, physical inactivity and consumption of tobacco, alcohol, drugs etc. are major global determinants of non-communicable diseases and contribute to the excess death and disability among the poor in terms of mortality. This study was done to estimate the prevalence of behavioral risk factors of NCDs among adolescent. Methods: A cross sectional study based on WHO stepwise approach for surveillance of Non- Communicable Diseases (NCDs) risk factors was conducted in Chitwan District to assess the risk factors of NCDs. Information was collected on substance abuse, dietary habits and physical activity through personal interview. Results: A bout 50% male and 30% female respondents were currently abusing one or other forms of substance. Male (39%) and female (26%) were using tobacco products. It was found that only 14% of respondents were doing satisfactory level of physical activities. Conclusions: Substantially high levels of the various behavioral risk factors among adolescents in Chitwan District suggest an urgent need for awareness raising programmes. DOI: http://dx.doi.org/10.3126/joim.v34i3.8916 Journal of Institute of Medicine, December, 2012; 34:39-43